Recent Trends in Inequality and Poverty in Developing Countries - Facundo Alvaredo; Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2013)
This chapter reviews the empirical evidence on the levels and trends in income/consumption inequality and poverty in developing countries. It includes a discussion of data sources and measurement issues, evidence on the levels of inequality and poverty across countries and regions, an assessment of trends in these variables since the early 1980s, and a general discussion of their determinants. There has been tremendous progress in the measurement of inequality and poverty in the developing world, although serious problems of consistency and comparability still remain. The available evidence suggests that on average the levels of national income inequality in the developing world increased in the 1980s and 1990s, and declined in the 2000s. There was a remarkable fall in income poverty since the early 1980s, driven by the exceptional performance of China over the whole period, and the generalized improvement in living standards in all the regions of the developing world in the 2000s.
Keywords: D31; I32; 330; inequality; poverty; income; consumption; developing countries